Thermotropic Properties and Molecular Packing of Discotic Tristriazolotriazines with Rigid Substituents. Issue 17 (12th March 2014) - Rieth, Thorsten; Marszalek, Tomasz; Pisula, Wojciech; Detert, Heiner
Abstract Tristriazolotriazines with a threefold dialkoxyaryl substitution have been prepared by Huisgen reaction of cyanuric chloride and the corresponding tetrazoles. Although these dyes show a negative or inverted solvatochromism of the UV/Vis absorption, their fluorescence is strongly positive solvatochromic. These discotic fluorophores are also emissive in their solid state and in their broad liquid‐crystalline mesophase. The structural study indicates that the thermotropic properties and organization of these systems can be well tuned by the steric demand of the aryl groups. Depending on the substituents, the compounds showed either a pure crystalline phase or a highly complex helical superstructure with a characteristic liquid‐crystalline phase at elevated temperatures. Changing the steric demand of the attached aryls allowed controlling the discs arrangement within the columnar helix, which is of great importance for the molecular orbital overlap.